Improvement of Hydrophilicity for Polyamide Composite Membrane by Incorporation of Graphene Oxide-Titanium Dioxide Nanoparticles - Thu Hong Anh Ngo; Chau Thi Minh Nguyen; Khai Dinh Do; Quan Xuan Duong; Nghia Hieu Tran; Hoan Thi Vuong Nguyen; Dung Thi Tran (Journal of Analytical Methods in Chemistry)
In this work, the polyamide (PA) membrane surface has been modified by coating of nanomaterials including graphene oxide (GO) and titanium dioxide (TiO2) to enhance membrane separation and antifouling properties. The influence of surface modification conditions on membrane characteristics has been investigated and compared with a base membrane. Membrane surface properties were determined through scanning electron microscope (SEM) images and Fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectroscopy. Membrane separation performance was determined through the possibility for the removal of methylene blue (MB) in water. Membrane antifouling property was evaluated by the maintained flux ratios (%) after 120 minutes of filtration. The experimental results showed that the appearance of hydrophilic groups after coating of GO and TiO2 nanocomposite materials with or without UV irradiation onto membrane surface made an improvement in the separation property of the coated membranes. The membrane flux increased from 28% to 61%; meanwhile, the antifouling property of the coated membranes was improved clearly, especially for UV-irradiated PA/GO-TiO2 membrane.